2008
DOI: 10.1002/jsfa.3208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inulin and Lactobacillus paracasei on sensory and instrumental texture properties of functional chocolate mousse

Abstract: BACKGROUND: This study evaluated the effect of a potentially probiotic bacteria (Lactobacillus paracasei subsp. paracasei LBC 82), added solely or together with the prebiotic ingredient inulin on instrumental texture attributes and sensory properties of a functional chocolate mousse during storage at 4 ± 1• C for up to 28 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 47 publications
4
30
0
4
Order By: Relevance
“…A broad range of ready-to-eat dairy desserts is available to the consumer, offering a wide variety of textures, flavours and appearances, and are regarded as attractive vehicles for the incorporation of probiotic cultures and other functional ingredients (Cardarelli, Aragon-Alegro, Alegro, Castro, & Saad, 2008). Nowadays, consumer interest in products that contribute to decreased risks of chronicdegenerative diseases encourages the development of dairy desserts containing functional ingredients, especially those that can also be employed as fat replacers, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A broad range of ready-to-eat dairy desserts is available to the consumer, offering a wide variety of textures, flavours and appearances, and are regarded as attractive vehicles for the incorporation of probiotic cultures and other functional ingredients (Cardarelli, Aragon-Alegro, Alegro, Castro, & Saad, 2008). Nowadays, consumer interest in products that contribute to decreased risks of chronicdegenerative diseases encourages the development of dairy desserts containing functional ingredients, especially those that can also be employed as fat replacers, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary, Majchrzak et al (2010) reported some sensory differences between probiotic and conventional yoghurts. Cardarelli et al (2008) emphasized that the chocolate mousse dessert is a suitable food for the delivery of bacterial probiotic strains with excellent viability and sensorial attributes. They also stated that, addition of Lb.…”
Section: Sensory Analysis Resultsmentioning
confidence: 99%
“…Probiotic microorganisms in level of 10 6 cfu g -1 of food at the time of consumption have been recommended as level to provide beneficial effects for consumers [33]. Several research findings have documented the probiotic carrier potential of both fermented and none fermented products [16,[34][35][36][37]. Fig-2] considering the pH drop necessary to preserve these products.…”
Section: Discussionmentioning
confidence: 99%